Political profit and the invention of modern currency - Dror Goldberg (Bar-Ilan University, Department of Economics, 2008)
The Massachusetts currency of 1690 was the first inconvertible paper money to be supported solely by a legal tender law. The circumstances that led to its creation exceed the typical story of wartime specie shortage. Due to temporary political constraints of that turbulent period, the currency could be neither backed by land nor granted a full legal tender status, as was then standard. Instead, it had to be disguised from England as a simple, private-like IOU. By pleasing both its pay-demanding troops and England, the government maximized its probability of survival subject to the constraints.
Keywords: 330; Papierwährung; Kolonialwirtschaft; Geldgeschichte; Währungssystem; Massachusetts